Tolerance to aluminium in apple rootstocks somaclones in nutrient solution - Dantas, Adriana Cibele de Mesquita; Fortes, Gerson Renan de Luces; Silva, João Baptista da; Nezi, Adriano Nunes; Rodrigues, Alexandre Couto (Pesquisa Agropecuaria Brasileira, 2001)
The apple trees (Malus sp.) cultivated in soils with pH below 5.0 may present nutritional disorders and growth restriction due to the presence of high toxic levels of Al that may affect the Ca absorption, which shows a narrow correlation with fruits of better quality. The aim of this work was to verify the tolerance to Al in 18 apple rootstocks somaclones and three cultivars originated from in vitro selection. The plantlets were cultivated in 300 mL plastic glasses with washed silica in nutrient solution for 45 days. The obtained values were submitted to a multivariate analysis by the main components and hierarchical grouping based on Ward method, which showed to be more appropriate to classify the clones with relationship to the tolerance to Al than the tests of averages. The reduction percentage in the dry matter of the shoots and in the number of leaves were characteristic that best permitted clones discrimination. Three groups of clones could be classified such as: no tolerant, slightly tolerant and tolerant.